Creating a Protective Shell for Reactive MoSi2 Particles in High‐Temperature Ceramics. Issue 8 (9th May 2015) - Carabat, Alexandra L.; van der Zwaag, Sybrand; Sloof, Willem G.; Troczynski, T.
<x xml:space="preserve">Abstract</x> Alumina encapsulated molybdenum silicide (MoSi2) intermetallic particles were synthesized using a simple precipitation method followed by calcining at temperatures of 800°C–1000°C, to prevent the premature oxidation of MoSi2 at high temperatures. The shell composition and the influence of the calcining temperature on microcapsule integrity were investigated by means of X‐ray photoelectron spectroscopy, X‐ray diffraction, scanning electron microscopy, and thermogravimetric analysis. The results demonstrate that the composition and the mechanical stability of the alumina shell can be tuned by the annealing temperature. After calcining at 800°C and 850°C the alumina shell remains intact. Calcining at higher temperature promotes the formation of mullite, which leads to cracking of the shell. However, when annealed at 1000°C for 24 h these cracks were filled with mullite and preserved the molybdenum silicide particles. Furthermore, the mechanical stability of the shell was improved by applying an intermediate calcining treatment at 450°C prior to the annealing process at 1000°C.